Constraints to bedside health education of diabetic patients at the University College Hospital, Ibadan Nigeria (2017)
The study examined institutional and personal factors as constraints to bedside health education of diabetic patients among nurses at the University College Hospital, Ibadan Nigeria. Descriptive survey research design was employed in the study. A sample of 50 respondents was selected using purposive sampling technique. Two research questions were answered and six research hypotheses were tested. Self-developed and validated questionnaire with reliability co-efficient of 0.89 was used to collect data. Data were analysed with the use of percentage and inferential statistics of chi-square at 0.05 level of significance. The result showed that workload, health education training programme, health education teaching aids, ward environment, attitude of nurses to patients and communication skills were constraints to bedside health education of diabetic patients. Provision of human and material resources are recommended to facilitate effective health education of hospitalised patients.